Construction of nested t-associate PBIB designs under restricted dualization - Philip, Jose; Banerjee, Shakti; Kageyama, Sanpei (Utilitas Mathematica, 1997)
A construction method of nested t-associate partially balanced incomplete block designs is proposed through restricted dualization by use of an irreducible balanced incomplete block design. In these designs, two collections of subblocks and superblocks form block designs with different association schemes.